Colonial Traumas, Indigenous Survivance: A Trans-Indigenous Literary Study - Bouich, A (University of Exeter, 2022)
This research explores representations of colonial trauma and Indigenous heal-ings in a selection of twenty-first-century Indigenous novels from different Indigenous cultural and geopolitical contexts and distinct literary traditions and genres across what is known today as North America and Australia. The four core chapters are divided into two interrelated, over-arching axes centred on Indige¬nous representations of colonial traumas and healing. The first, comprising chap¬ters One and Two, investigates literary representations of colonial traumas in Indigenous fiction by considering the structural/material and subjec-tive/psychological dimensions of colonial domination within particularities of set-tler-colonial structures and histories of dispossession. Chapter One explores There There (2018) by Cheyenne novelist Tommy Orange and Taboo (2017) by Noongar writer and activist Kim Scott. It investigates narrative registers and aes-thetic techniques employed by the authors to inscribe traumas of colonial moder-ni¬ty experienced by the Indigenous communities represented in their nov¬els within the broader settler-colonial structures and histories of dispossession. Chapter Two examines representations of the psycho-affective dimension of co-loni¬al oppression in Indian Horse (2012) by Ojibwe writer and journalist Richard Wagamese and Swallow the Air (2006) by Wiradjuri writer Tara June Winch, fo-cus¬ing on the registration of the traumatic impact of racism. The second part, comprising chapters Three and Four, addresses representations of healing in Indige¬nous futurisms and wonderworks, attending to their aesthetic mobilisation of specific Indigenous epistemologies, ontologies, and worldviews to present nar-ra¬tives of Indigenous survivance that reflect Indigenous decolonial perspec¬tives on sovereignty in its material, cultural, and subjective dimensions. Chapter Three approaches two works of Indigenous futurisms: Killer of Enemies (2013) by Abenaki writer Joseph Bruchac and The Interrogation of Ashala Wolf (2012) ...